A Survay Of The Availability And Utilization Pattern Of Information And Communication Technology By French Language Teachers In Upper Basic Classes In Edo State - Alufohai, Peace Joan; J. I., Asika (Advances in Social Sciences Research Journal, 2019)
The study adopted the survey design to assess teachers’ use of information and communication technology in public secondary schools in Edo State. Purposive sampling technique was used to draw the sample for the study. The questionnaire titled Information and Communication Technology Availability and Utilization by French Language Teachers’ Questionnaire (ICTAUFLTQ) was used to elicit information from the teachers (respondents). Data were analyzed using frequency count and simple percentage. Findings revealed that availability of computer and internet facilities, competency level of teachers on information and communication technology was very low and inadequate to cope with the recent trend. Recommendations were made and it include the fact that government needs conscious responsibility by providing adequate information and communication gadgets/facilities to the nation’s upper basic classes for the effective implementation of the French language curriculum.